Thymic stromal lymphopoietin is a key cytokine for the immunomodulation of atherogenesis with Freund's adjuvant. Issue 10 (13th April 2020) - Steinmetz, Martin; Laurans, Ludivine; Nordsiek, Sarah; Weiß, Lena; van der Veken, Bieke; Ponnuswamy, Padmapriya; Esposito, Bruno; Vandestienne, Marie; Giraud, Andreas; Göbbel, Cristina; Steffen, Eva; Radecke, Tobias; et al.
Abstract: Adaptive immune responses regulate the development of atherosclerosis, with a detrimental effect of type 1 but a protective role of type 2 immune responses. Immunization of Apolipoprotein E‐deficient (ApoE −/− ) mice with Freund's adjuvant inhibits the development of atherosclerosis. However, the underlying mechanisms are not fully understood. Thymic stromal lymphopoietin (TSLP) is an IL7‐like cytokine with essential impact on type 2 immune responses (Th2). Thymic stromal lymphopoietin is strongly expressed in epithelial cells of the skin, but also in various immune cells following appropriate stimulation. In this study, we investigated whether TSLP may be crucial for the anti‐atherogenic effect of Freund's adjuvant. Subcutaneous injection of complete Freund's adjuvant (CFA) rapidly led to the expression of TSLP and IL1 β at the site of injection. In male mice, CFA‐induced TSLP occurred in immigrated monocytes—and not epithelial cells—and was dependent on NLRP3 inflammasome activation and IL1 β ‐signalling. In females, CFA‐induced TSLP was independent of IL1 β and upon ovariectomy. CFA/OVA led to a more pronounced imbalance of the T cell response in TSLPR −/− mice, with increased INF γ /IL4 ratio compared with wild‐type controls. To test whether TSLP contributes to the anti‐atherogenic effects of Freund's adjuvant, we treated ApoE −/− and ApoE −/− /TSLPR −/− mice with either CFA/IFA or PBS. ApoE −/− mice showed less atherogenesis upon CFA/IFA compared with PBS injections. ApoE −/− /TSLPR −/− mice had no attenuation of atherogenesis upon CFA/IFA treatment. Freund's adjuvant executes significant immune‐modulating effects via TSLP induction. TSLP‐TSLPR signalling is critical for CFA/IFA‐mediated attenuation of atherosclerosis.